The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1186/1471-2105-8-243
|View full text |Cite
|
Sign up to set email alerts
|

Automatic extraction of gene ontology annotation and its correlation with clusters in protein networks

Abstract: Background: Uncovering cellular roles of a protein is a task of tremendous importance and complexity that requires dedicated experimental work as well as often sophisticated data mining and processing tools. Protein functions, often referred to as its annotations, are believed to manifest themselves through topology of the networks of inter-proteins interactions. In particular, there is a growing body of evidence that proteins performing the same function are more likely to interact with each other than with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 49 publications
(39 reference statements)
0
31
0
Order By: Relevance
“…All of them were created by manual curation and therefore have limited scope and usability. The results of information extraction by manual curation and by NLP technology were compared previously [3,4]. In brief, they concluded that NLP provides significantly higher recovery rate and consistency of extracted data while manually curated dataset usually provides higher accuracy.…”
Section: Overview Of the Marketmentioning
confidence: 99%
“…All of them were created by manual curation and therefore have limited scope and usability. The results of information extraction by manual curation and by NLP technology were compared previously [3,4]. In brief, they concluded that NLP provides significantly higher recovery rate and consistency of extracted data while manually curated dataset usually provides higher accuracy.…”
Section: Overview Of the Marketmentioning
confidence: 99%
“…Therefore, biomedical researchers always wish to explore the pathogenesis of abnormal expressing genes, such as those genes confirmed by cDNA microarray analysis, and furthermore, literature mining is an important method for completing them [7]. At present, there have been a variety of mining tools and methods to extract keywords from literatures or gene networks from functional genes and to make them visualized [8][9][10][11][12][13][14][15]. However, based on specific keywords, these tools cannot automatically and simply establish gene networks that are helpful to explore diseaserelated signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Option " " is the value to conduct the inflation and expansion in the Markov model; thus, it is possible to see the changes of elements inside the clustering depending on the value of . Another function prediction method is the context-free method; it utilizes the context of several DBs of Uniprot or PubMed [15].…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%